Societal response to monsoon variability in Medieval South India: Lessons from the past for adapting to climate change. (August 2017) - Shanmugasundaram, Jothiganesh; Gunnell, Yanni; Hessl, Amy E; Lee, Eungul
Future climate change will challenge society's ability to adequately manage water resources, particularly in the developing world. The response of past societies to climatic variability, particularly in terms of water management, can provide useful insights into the timing and scale of response to future events. We present a regional case study from South India to illustrate the influence of climate on shaping the rise and economic prosperity of the Chola Kingdom from 850 to 1280ce – a period approximately coinciding with the Medieval Climatic Anomaly. An investigation of instrumental and proxy climatic data sets between 500 and 2010ce indicates that the period between 850 and 1300ce, a time of frequent El Niño-like conditions, was associated with a substantial increase in North-East Indian monsoon rainfall (NEIMR), whereas South-West Indian monsoon rainfall (SWIMR) suffered substantial deficits. The spatial pattern and chronology of water harvesting infrastructure development under Chola rule indicate that these features were concentrated in the NEIMR-receiving regions of southeastern India and that their construction peaked during El Niño-dominated intervals. Overall, enhanced NEIMR conditions and adaptation strategies practiced in the Chola's territory, combined with less favorable climatic conditions over the neighboring kingdoms, appears to have underpinned the well-documented political and economic strengths of the Chola superpower. We infer that the water management infrastructure promoted by the Chola rulers helped to buffer the consequences of climatic extremes in later history, whether droughts (e.g. the El Niño-related mega-drought of 1876–1878) or floods (because the reservoirs can contain surplus runoff). More recently, however, a preference for groundwater irrigation and other landscape changes driven by population pressure has made the region more vulnerable to the incidence of heavy NEIMR episodes, as illustrated by the severe floods of 2015. Future climate adaptation planning in South India should appreciate the merits of restoring and expanding the currently decaying legacy of Chola-style 'no regrets' water management infrastructures.